Single bead near-infrared random laser based on silica-gel infiltrated with Rhodamine 640 - Moura, André L.; Barbosa-Silva, Renato; Dominguez, Christian T.; Pecoraro, Édison [UNESP]; Gomes, Anderson S. L.; De Araújo, Cid B. (AIP Publishing, 2018)
Photoluminescence properties of single bead silica-gel (SG) embedded with a laser-dye were studied aiming at the operation of near-infrared (NIR) Random Lasers (RLs). The operation of RLs in the NIR spectral region is especially important for biological applications since the optical radiation has deep tissue penetration with negligible damage. Since laser-dyes operating in the NIR have poor stability and are poor emitters, ethanol solutions of Rhodamine 640 (Rh640) infiltrated in SG beads were used. The Rh640 concentrations in ethanol varied from 10-5 to 10-2 M and the excitation at 532 nm was made by using a 7 ns pulsed laser. The proof-of-principle RL scheme herein presented was adopted in order to protect the dye-molecules from the environment and to favor formation of aggregates. The RL emission from ≈650 nm to 720 nm, beyond the typical Rh640 monomer and dimer wavelengths emissions range, was attributed to the trade-off between reabsorption and reemission processes along the light pathways inside the SG bead and the contribution of Rh640 aggregates.